The association between sleep apnea and young adult with hypertension: a case-control study in Malaysia - Asha'ari, Zamzil Amin; Hasmoni, Mohamed Hadzri; Ab Rahman, Jamalludin; Yusof, Rosnida Azura; Raja Lope Ahmad, Raja Ahmad Al'konee (2012)
Objectives: To study the association between sleep apnea and hypertension in a younger age group than previously studied. Methods: We analyzed data on sleep-disordered breathing (based on polysomnography tests), body mass index (BMI), neck circumference, upper airway endoscopy sizes, and habitus and health history in 120 hypertensive and 120 nonhypertensive participants in a clinic-based setting. Independent t test, chi-square, multivariate analysis, and binary logistic regression models were used for case-control comparison. Age group of the participants were 18-40 years. Results: Persons with hypertension had an OR of 2.7 times of having comorbid sleep apnea than patients without hypertension (95% confidence interval [CI] 1.2-6.1). Persons with sleep apnea (AHI [apnea-hypopnea index] 5) had an OR of 2.76 (95% CI 1.57-4.86), and persons with severe sleep apnea (AHI 30) had an OR 7.94 (95% CI 4.21-15.33) for having hypertension than did persons without sleep apnea. Although adjustments for the compounding factors, particularly BMI, decreased the OR to a large degree, subjects with severe sleep apnea were still 72% more likely to have hypertension than subjects without sleep apnea (Table 1). Conclusions: Sleep apnea is related to hypertension in the young adults. The association was more pronounced with the increasing severity of sleep apnea. Screening for sleep apnea should be considered in young adults with hypertension.